Anemia and Aggression Among Patients with Schizophrenia in Amino Gondohutomo Psychiatric Hospital - Noerhidajati, Elly; Sofa, Yulia Ratna; Woroasih, Sri; Hardini, Intan Tri (International Journal of Integrated Health Sciences, 2025)
Background: Anemia has been identified as a potential modifiable factor influencing aggression levels in individuals with schizophrenia.Objective: To investigate the association between anemia and incidence of aggression in patients with schizophrenia in Amino Gondohutomo Psychiatric Hospital, Semarang, Indonesia.Methods: A cross-sectional study was conducted between January 2022 and December 2023 on patients with schizophrenia in Amino Gondohutomo Psychiatric Hospital, Semarang, Indonesia. Subjects were selected using consecutive sampling technique, and individuals with affective mood disorder and lost to follow-up were excluded from the study. Data were obtained through patients’ medical records, PANSS-EC scores, and hemoglobin measuring devices. Chi-square test and logistic regression were applied for statistical analyses.Results: Of 100 participants, patients with schizophrenia presented with aggression were predominantly above 40 years old (26 patients, 81.3%), women (17 patients, 51.1%), and non-anemic (17 patients, 57.1%). Gender and anemia were significantly associated with aggression in patients with schizophrenia (p <0.05). Schizophrenic patients with anemia had a 7.68-fold greater risk (95% CI: 2.70 – 21.8) of aggression. Men with schizophrenia was associated with a 2.37-fold greater risk (95% CI: 1.00 – 5.60) of aggression.Conclusion: Anemia and men seems to be risk factors of aggression in patients with schizophrenia. Further multicenter studies with larger sample size is needed to support this finding.